Application of Rebuke Therapy to Control Auditory Hallucinations in Patients with Schizophrenia - Prawesty Desy Nugraheni; Ita Apriliyani (Viva Medika, 2024)
Various abnormal mental and physical conditions combine to form mental disorders. Delusions, hallucinations and erratic behavior are characteristics of a serious mental disorder known as schizophrenia. Hallucinations, one of the signs of mental illness, are distorted perceptions of a person's senses, including hearing, sight, touch, taste, and smell. One alternative for treating hallucinations with medication is the scolding technique. This research uses a case study methodology. Individuals suffering from auditory hallucinations and sensory perception disorders auditory hallucinations in room lyly 9 RS. Prof.'s soul Dr. Soerojo Magelang. Results: Implementation of rebuke therapy in clients with auditory hallucinations for 3 days can control when the hallucinations appear. These results indicate that rebuke therapy is effective in controlling hallucinations